Aspects of the financial crisis in higher education in Colombia (2013)
The current situation on the relevance or otherwise of the reform of higher education that is a response to the crisis in the sector due to the high costs of sustaining the nation for the current model, this added to the country's needs in terms of training for citizens and deconcentration of the offer to reach the most remote regions of the country to comply with the principle of equal access to higher education, the current situation of the sector shows a structural lag on resources that should receive higher education institutions considering the increasing requirements to implement state policies, in this regard are the international benchmarks of how higher education is managed in countries similar to ours and chapters from the proposed funding reforms to the law 30 92